Prática de atividade física e suporte social em adolescentes : um estudo de base populacional - Peixoto, Márcio Botelho (2012)
The aim of the study was to evaluate the association between leisure-time physical activity and social support (from relatives and from friends) among adolescents aged 10 to 19 years. This was a population-based cross-sectional study carried out in the city of Pelotas, Brazil. Adolescents were considered as active in leisure-time if reporting to practice 300 min/wk or more of physical activity. Social support was assessed through the Physical Activity Social Support Scale. The study included 743 adolescents. The proportion of active adolescents was 28.2% (95%CI 24.6-31.3). Boys who report to have higher social support from friends were 68% more likely to achieve physical activity recommendations as compared to their peers reporting no such social support. Girls with high scores of social support from the family were 210% more likely to be active than those without such a support. The equivalent proportion for boys was 46%. Social support from relatives and friends towards physical activity practice strongly influences the behavior of adolescents.